Cross-sectional study on the epidemiological investigation ability of professional staff from Centers for Disease Control and Prevention in Guizhou Province - Huang, He; Yao, Guang-hai; Huang, Jiao; Deng, Bin; Wu, Jun; Yu, Chun (Frontiers in Public Health, 2024)
This study aims to evaluate the qualifications and identify skill enhancement areas for epidemiological investigators in Centers for Disease Control and Prevention (CDCs) in Guizhou's, informing future training and policy initiatives to strengthen public health responses. A cross-sectional survey was conducted in August 2022, and to determine the number of qualified epidemiological investigators in Centers for Disease Control and Prevention (CDCs)in Guizhou and the strategies to enhance their skills. An an online, self-designed questionnaire on the Epidemiological Dynamic Data Collection platform was administered to evaluate the professional staff in CDCs. The responses were scored and presented using descriptive statistical methods, and the factors influencing the total score were analyzed by one-way ANOVA and linear regression. A total of 1321 questionnaires were collected, yielding an average score of 14.86±3.49 and a qualification rate of 29.9%. The scoring rate of ability of individual protection and coordination in epidemic control was high (87.25%). Meanwhile, improvements in further training were needed in areas such as data analysis ability (23.67%), knowledge of site disinfection (40.40%), and epidemiological investigation skills (42.50%). No significant difference was observed between the scores of city and county CDCs, (t=1.071, p=0.284). The effects of gender and age could be disregarded, and the experience in epidemiological work and training (including investigation on COVID-19 cases and contacts), educational background, and professional title partially explained the survey outcome (R Square of the linear regression model was 0.351). The survey indicated the need for additional well-trained epidemiologic investigators in Guizhou. Specified training was effective in improving epidemiologic investigation, and enhancement in data analysis ability and knowledge of field disinfection are recommended should be enhanced in professional staff cultivation.